ANALISIS KEBUTUHAN WALI MURID TERHADAP SEKOLAH FULL DAY (Jurnal Sosial Humaniora dan Pendidikan, 2023)
The community's need for full day schools is increasing every year. There are many factors behind this, what is interesting to research is the reasons why parents choose to send their children to full-day school. The author took the example of a full day school in West Kotawaringin district, specifically the Integrated Islamic School. There are two foundations (schools) that implement a full day school system in West Kotawaringin district, namely SIT Al Manar and SIT Cendikia. This type of research is descriptive qualitative, that is, the data collected is in the form of words, images, not numbers. The author made observations and acted as an active observation participant, interviewing parents at both institutions. Then analyze and reduce the data obtained from the field. The results of this research show that what parents need for full day school is for their children to get the right education. Who is not only academically intelligent, but also has character, is socially and emotionally intelligent, and also understands his religion well. Also an equally important reason is that parents want their children to have a good environment when their children are left behind to work.